An injectable degradable porous polymer scaffold for tissue engineering and drug delivery - Salem, Aliasger K. (2002)
Cell transplantation on biodegradable scaffolds is an established approach in tissue engineering to the problem of the regeneration of diseased or damaged tissues. As cells grow and organise themselves, they secrete their own extracellular matrix, while the polymer degrades into natural metabolites resulting in eventual natural tissue replacement. Polymeric materials used for these scaffolds must satisfy a number of requirements. These include defined cell-interactive properties, porosity, biodegradability, mechanical and controlled release properties.